Perceptions of Technical Debt and Its Management Activities - A Survey of Software Practitioners - Albuquerque, Danyllo; Guimaraes, Everton Tavares; Tonin, Graziela Simone; Perkusich, Mirko Barbosa; Almeida, Hyggo; Perkusich, Angelo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Technical Debt (TD) is a metaphor reflecting technical compromises that can yield short-term benefits but might hurt the long-term health of a software system. Although several research efforts have been carried out, TD-related literature indicates that Technical Debt Management (TDM) is still incipient. Particularly in software organizations, there is still a lack of knowledge regarding how practitioners perceive TD and perform TDM in their projects. Our research focuses on characterizing TD and its management under the perspective of practitioners. For doing so, we conducted an online survey with 120 participants from 86 different organizations located in 5 different countries. Our results indicate that TD conception is widespread among more than 70% of respondents. Most of them (72%) recognized its importance and impact on software artifacts, being able to provide a valid example of three different TD Types (i.e., Design, Code, and Architectural). In addition, at least 65% of respondents consider TD identification, TD Repayment, and TD prevention as TDM activities in the spotlight. However, less than 15% adopt formal approaches to support these activities. This paper contributes to TD discussion and TDM activities by showing the practitioner’s perspective. Finally, further research will support observing how effective and efficient TDM activities can be in different contexts.